Advanced Chromatographic Techniques For Pesticide Determination In Biological Specimens: Precision Approaches In Analytical Toxicology - Kanawade, Madhuri B.; Kachave, Ramanlal N.; Chavan, Macchindra J. (Journal of Neonatal Surgery, 2025)
Pesticides are crucial in preventing vector-borne diseases, protecting crops, and preserving food, thus playing a noteworthy role in sustaining global food production. The use of pesticides is expected to increase substantially, with projections indicating a rise to nearly 10 billion metric tons by 2050. Despite their benefits, pesticides raise concerns because of their potential effects on human health and the environment. Only around 1% of applied pesticides effectively reach the targeted pests, whereas the remaining 99% disperse into soil, water, and surrounding ecosystems, affecting non-target organisms. This widespread contamination has been associated with severe health risks, especially for agricultural workers and vulnerable populations like children. Chronic pesticide exposure often raises the threat of cancers, neurological disorders, and respiratory issues. Environmentally, pesticides harm biodiversity, degrade soil health, and cause a decline in pollinator populations, which are vital to ecosystem balance. To monitor and mitigate these risks, advanced chromatography techniques, particularly gas chromatography-mass spectrometry (GC-MS), liquid chromatography-tandem mass spectrometry (LC-MS/MS), and UHPLC-MS are widely used for the detection of pesticide residues in biological specimens, including blood and urine. These advanced techniques offer high sensitivity, specificity, and precision, making them essential for assessing human exposure, supporting public health studies, and meeting regulatory standards. This review delves into the complexities of pesticide exposure, recent advancements in chromatographic detection, and emerging strategies in residue analysis, emphasizing the need for ongoing innovation to enhance pesticide monitoring and safeguard the health and the environment